Analysis of Entrepreneurship Development Model on Micro, Small and Medium Enterprises Entities in Badung Market Area, Denpasar City - Oktiviantari, Ni Wayan; Prianthara, IB. Teddy (Institut Pariwisata dan Bisnis Internasional, 2020)
This research aims to observe the efforts done by the MSME (Micro, Small and Medium Enterprises) entities in developing the entrepreneurship and to observe the difficulties which were encountered by the MSME entities in the process of entrepreneurship development. This research was designed by using a qualitative approach. The location of this research is in the area of Badung Market in Denpasar City. The primary data is obtained through the research informants. The informants in this research are the MSME entities in Badung Market area in Denpasar. The data validation testing was done using data triangulation. The data were analyzed using the descriptive qualitative technique. The result shows that the entrepreneurship model which is done in Badung Market is based on the togetherness concept. This togetherness concept means the concept is of the people, by the people and for the people. The development process makes the MSME entities in Badung Market, Denpasar more creative and aware in seeing any opportunities to open a new business. This process is certainly influenced by many factors, both internal and external such as, education, sociology, organization, tradition and environment. Those factors formed locus of control, creativity, innovation, implementation, and growth which then will develop to become a great entrepreneur. The development process is divided into some development stages which are innovation process, support process, implementation process and growth process.